Introduction to Special Section on Oceanic Responses and Feedbacks to Tropical Cyclones. Issue 2 (16th February 2018) - Zhou, Lei; Chen, Dake; Karnauskas, Kristopher B.; Wang, Chunzai; Lei, Xiaotu; Wang, Wei; Wang, Guihua; Han, Guijun
Abstract: Tropical cyclones (TCs) are among the most destructive natural hazards on Earth. The ocean can have dramatic responses to TCs and further imposes significant feedbacks to the atmosphere. A comprehensive understanding of the ocean‐TC interaction is a challenging hindrance for improving the simulation and prediction of TCs and therefore avoidance of human and economic losses. A special section of JGR‐Oceans was thus organized, in order to have a broad summary of latest progress in ocean‐TC interactions. This introduction presents a brief overview of the contributions found in this collection. We hope it can also shed light on recent advance and future challenges in the studies on the oceanic responses and feedbacks to TCs. Key Points: The special section on ocean‐TC interaction in JGR‐Oceans is introduced Papers in the special section are briefly reviewed and some papers are highlighted Challenges and suggestions for further studies in ocean‐TC interactions are presented